Comportamento de minérios de ferro na concentração por flotação na presença de lamas - Michelle Lacerda Sales Marques (2013)
The deleterious effect of slimes on the flotation performance is recognized, but the understanding of the interaction mechanism between the slimes and the ore is complex. Thus, tests were carried out in the presence of different amounts of slimes with different mineralogical compositions to explain the effect promoted by the slimes in the flotation process. Physico-chemical conditions similar to those used in the industry were aimed, regarding the reagents utilized. Various characterizations were performed to try to explain the mechanism of interaction of the slime with the ore Flotation experiments were performed with three samples of itabirite ores, one of them from Conceição mine, other from Fábrica Nova mine and another composed of a blend between Sapecado and Galinheiro mines, all with distinct mineralogical characteristics. Four samples were selected from distinct slurries which also were generated from three of these ore samples and a fourth sample from a goethitic itabirite from Alegria mine. The second phase of the study evaluated the effect of these same slimes on two samples being one composed mainly of iron minerals and other consist of quartz.The slimes samples originating from the mines of Fábrica Nova and Alegria are the ones that had higher contents of goethite, but less influence on the results of flotation ores studied. The slime coming from the sample Conceição was the one that caused the greatest impact particularly on flotation of its own ore. For a sample consisting essentially of iron minerals was shown that the increase in dosage causes greater flotability of the fine particles and the sample composed mainly of quartz was observed a distinct result from the fraction above 0,075 mm when increasing the dosage of the collector or addition of dispersant reduced to flotability this mineral. From the analysis of the samples specific surface area, zeta potencial and the flotation results it is possible to conclude that those characteristics were not the factors responsible for the variations in the silica contents in the concentrate. For all tests with similar amounts of slimes the measured values of specific surface area were similar and the zeta potencial for those slimes was similar in the pHs flotation.